A preliminary screening of antifungal activities from skin mucus extract of Malaysian local swamp eel (Monopterus albus) - Mohamed Nor, Nik Mohd Ikram; Hashim, Ridzwan (International Research Journals, 2013)
A preliminary screening of antifungal activities of skin mucus extract from Malaysian local swamp eel, Monopterus. Albus was performed. The eel’s skin mucus was extracted using two aqueous extraction solvents; distilled water and Phosphate Buffer Sali ne (PBS). In addition, pure mucus was also applied without any extraction process. Each extract was pr epared in different concentration via 10-fold seria l dilution and applied onto an agar containing cultur ed fungi using a blank diffusion disc. The method utilized was the disc diffusion sensitivity assay. The tested pathogenic fungi were Candida albicans , Candida krusei , Cryptococcus neoformans and Fusarium spp. PBS extract and pure mucus showed no zone of inhibition for all tested fungi. Water extr act of skin mucus revealed an inhibitory effect on all the fungi whereby Fusarium spp. Was observed to be the most sensitive. The zo ne of inhibition varies from as low as 8 mm to as high as 20 mm but was still de pendent on the incubation period. It was also observed that water acted as a more effective solve nt to extract possible antifungal compound from the skin mucus of M. albus . Throughout, it is suggested that freshwater eel p ossess antifungal activity from its skin mucus and thus supported the claims among locals